Kaija Saariaho - Moisala, Pirkko (Book collections on Project MUSE., 2009)
This book is the first comprehensive study of the music and career of contemporary composer Kaija Saariaho. Born in Finland in 1952, Saariaho received her early musical training at the Sibelius Academy, where her close circle included composer and conductor Esa-Pekka Salonen. She has since become internationally known and recognized for her operas L'amour de loin and Adriana Mater and other works that involve electronic music. Her influences include the spectral analysis of timbre, especially string sounds, micropolyphonic techniques, the visual and literary arts, and sounds in the natural world. Pirkko Moisala approaches the unique characteristics of Saariaho's music through composition sketches, scores, critical reviews, and interviews with the composer and her trusted musicians. Drawing extensively from this material, Moisala describes the development of Saariaho's career and international reception, the characteristics of her musical expression, and the progression of her compositional process.